Effects of inhalation and intravenous administration of allogeneic mesenchymal bone marrow stromal cells in a bleomycin-induced model of pulmonary fibrosis in rabbits - A. V. Averyanov; A. G. Konoplyannikov; F. G. Zabozlaev; O. V. Danilevskaya; M. A. Konoplyannikov; A. V. Sorokina; I. A. Koroleva; N. S. Antonov; G. L. Osipova; O. S. Vasilyeva; G. M. Sakharova; A. R. Tatarsky; et al. (Вестник трансплантологии и искусственных органов)
Aim: to perform a comparative analysis of the efﬁ cacy of the inhaled and intravenous delivery of equivalent doses of bone marrow mesenchymal stem cells (BMMSCs) in rabbits according to the standard model of bleomycin pulmonary ﬁ brosis.Materials and methods. After bronchoscopic instillation of bleomycin, 5 rabbits received intravenous transplantation of 2 × 106 allogeneic BMMSCs, other 5 rabbits – 2 × 107 MSCs inhaled via compressor nebulizer; control healthy and bleomycin group included 5 animals each.Results. Both groups treated with BMMSCs had a signiﬁ cantly lower Ashcroft ﬁ brosis index than the bleomycin control group. Expression of collagen in lung tissue in all groups with bleomycin injury was superior to healthy controls, but in animals underwent intravenous BMMSC transplantation collagen score was 0.74 points, and in inhaled treated group – 0.51 points, while in bleomycin controls – 2.1 point. Levels of TNF-α and TGF-β1 in BAL ﬂ uids tended to decrease in treatment groups, but did not differ signiﬁ cantly from control. A similar picture was observed in the cytological analysis of BAL.Conclusion. In general, both methods of delivering of BMMSCs to the lungs demonstrated similar therapeutic effects in inhibiting the development of experimental ﬁ brosis, indicating that both intravenous and inhalational way of introduction can be used for subsequent clinical studies.